Japanese Popular Culture in the Formation of Malaysian Youth Identity and Aspirations - Nunuk Endah Srimulyani; Paidi, Rohayati (WILAYAH: The International Journal of East Asian Studies, 2025)
This study explores how Japanese popular culture shapes the identities, relationships, and aspirations of Malaysian youth. While Japanese popular culture is widely consumed, prior research has often been descriptive, with limited focus on how fandom is enacted, recognised, and projected into the future. Using a qualitative approach, twenty university students were interviewed via WhatsApp, and their experiences analysed through thematic coding and quadrant mapping of engagement and future alignment. The analysis was guided by an integrated framework combining Identity Theory, Self-Verification Theory, Narrative Identity Theory, and Future Self-Continuity Theory. Findings show that fandom identities are fluid, socially endorsed, narratively constructed, and future-oriented. The High engagement–High future quadrant dominated, with participants translating practice and recognition into concrete pathways such as creative portfolios, animation degrees, or Japanese language study. Conversely, private leisure characterised the Low engagement–Low future group. The absence of High engagement–Low future participants indicates that sustained engagement rarely exists without future projection.